Clinical presentation of autoimmune disorders in pregnancy - Singhal, Neha; Gupta, Alka S.; Prasad, Madhva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Autoimmune disorders have a significant impact over the health of an individual. This heterogenous group of disorders affects pregnancy in a multitude of ways. Pregnancies with autoimmune disorders are usually cared for by a multidisciplinary team of doctors. Methods: Pregnancies with autoimmune disorders were studied over a one-year period in one unit of a medical college teaching hospital set up. Obstetric and neonatal outcomes were studied. Results: Ten patients were studied. Average age was 29.9 years. Majority presented in early second trimester. Eight patients were ANA positive. Two patients had antiphospholipid antibody syndrome, for whom low molecular weight heparin was helpful. Hypothyroidism was seen in two patients. Bad obstetric history was seen in most patients. Successful neonatal outcome was seen in six patients. One patient had Evans syndrome. There were no maternal mortalities. There was one perinatal mortality. Conclusions: Autoimmune disorders in pregnancy when managed in a tertiary care centre with multidisciplinary approach can result in good obstetric and neonatal outcomes.